Pengaruh penambahan Ekstrak Biji Kelor sebagai Antioksidan Masker Gel peel off - Sari, Fatma; Sari, Alvika Meta; Nugrahani, Ratri Ariatmi; Kurniaty, Ika; Putri, Dirga Aulia Eka (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Compounds called antioxidants are particularly beneficial to human health. Antioxidant substances are frequently utilized as free radicals because they can prevent the growth of oxidation reactions. Because of their high antioxidant content, moringa seeds produce oil that is resistant to rancidity and does not easily oxidize.  The peel-off gel mask formulation in this investigation included Moringa seed oil extract as a source of natural components. The goal of this study was to evaluate the antioxidant activity of a peel-off gel mask preparation made from Moringa seed oil extract. Maceration extraction is the technique used for extraction, and DPPH is the technique used to test for antioxidants. The results showed that the sample with a solvent volume of 450 ml had the best yield (34.64%), and the antioxidant activity of the extract of Moringa seed oil was measured at 256.89 g/ml with an average pH of 5.79.  The Moringa seed oil extract peel-off gel mask has the attributes of being white, thick, and smelling like moringa seeds. The peel-off gel mask gets thicker the more Moringa seed oil extract there is in it. This study establishes the potential of using Moringa seed oil extract in peel-off gel mask formulations extract in peel-off gel mask formulations.